Bedside clinical assessment predicts recurrence after hospitalization due to viral lower respiratory tract infection in young children (2020)
Infants requiring hospitalization due to a viral lower respiratory tract infection (LRTI) have a high risk of developing recurrent respiratory illnesses in early life and asthma beyond childhood. Notably, all validated clinical scales for viral LRTI have focused on predicting acute severity instead of recurrence. We present a novel clinical approach combining individual risk factors with bedside clinical parameters to predict recurrence after viral LRTI hospitalization in young children. A retrospective longitudinal cohort of young children (≤3 years) designed to define clinical predictive factors of recurrent respiratory illnesses within 12 months after hospitalization due to PCR-confirmed viral LRTI. Data collection was through electronic medical record. We included 138 children hospitalized with viral LRTI. Using automatic stepwise logistic model selection, we found that the strongest predictors of recurrence in infants hospitalized for the first time were severe prematurity (≤32 weeks’ gestational age, OR=5.19; 95% CI 1.76 to 15.32; p=0.002) and a clinical score that weighted hypoxemia, subcostal retractions and wheezing (OR=3.33; 95% CI 1.59 to 6.98; p<0.001). After the first hospitalization, the strongest predictors of subsequent episodes were wheezing (OR=5.62; 95% CI 1.03 to 30.62; p=0.04) and family history of asthma (OR=5.39; 95% CI 1.04 to 27.96; p=0.04). We found that integrating individual risk factors (eg, prematurity or family history of asthma) with bedside clinical assessment (eg, wheezing, subcostal retractions or hypoxemia) can predict the risk of recurrence after viral LRTI hospitalization in infants. This strategy may enable clinically oriented subsetting of infants with viral LRTI based on individual predictors for recurrent respiratory illnesses during early life.